Longevity of immediate rehabilitation with direct fiber reinforced composite fixed partial dentures after up to 9 years. (September 2020) - Perrin, P.; Meyer-Lueckel, H.; Wierichs, R.J.
Abstract: Objectives: This retrospective, single-center, practice-based cohort study aimed to analyze the longevity of direct fiber reinforced composite fixed partial dentures (DFRC-FPD) and to analyze factors influencing their survival and success. Methods: Within one private practice 100 DFRC-FPD were directly applied. The preparation of a proximal cavity was limited to abutment teeth with an existing filling (minimal-invasive approach). All intact enamel surfaces were preserved (micro-invasive approach). DFRC-FPD were reinforced by fiber-splints with semi polymer network matrices (Everstick C + B©). At the last follow-up DFRC-FPD were considered successful if they were still in function without any need of therapy. DFRC-FPD were considered as survived if they were repaired or replaced. Multi-level Cox proportional hazard models were used to evaluate the association between clinical factors and time. Results: Within a mean follow-up period (range) of 53 (2-109) months 7 bridges did not survive (cumulative survival rate: 93%) and further 24 bridges had received a restorative follow-up treatment (cumulative success rate: 69%). The annual failure rate was 1.6% for survival and 8.3% for success. The main failure type was fracture of the composite material (n = 30). In multivariate analysis no significant predictor could be found for success and survival. Conclusions: For directly prepared fiber reinforced composite bridges high survival and moderate success times were observed after up to nine years. Based on the present results DFRC-FPD might be an immediate, short- to medium-term solution for replacing 1 to 2 missing teeth with no or minimal tooth preparation. Clinical significance: Within the limitations of the present study DFRC-FPD offered an immediate, micro-/minimal-invasive, inexpensive short- and medium-term solution to replace missing teeth, even if no box-shaped proximal cavity was prepared.